Insights into the hydrocarbon and carbon monoxide emissions in moderately and highly dilute Low Temperature Combustion. (September 2014) - Sogbesan, Oluwasujibomi; Davy, Martin H; Garner, Colin P
Low-temperature combustion in diesel engines offers attractive benefits through simultaneous reduction in the nitrogen oxide emissions and the soot emissions. However, it is known that the in-cylinder conditions typical of low-temperature combustion operation tend to produce high emissions of unburned hydrocarbons and carbon monoxide, reducing the combustion efficiency. The present study develops from the hypothesis that this characteristic poor combustion efficiency is due to the in-cylinder mixture preparation strategies which are non-optimally matched to the requirements of the low-temperature combustion mode. In this work, the effects of three key fuel path parameters, namely the injection fuel quantity ratio, the dwell and the injection timing, on the carbon monoxide and hydrocarbon emissions were examined using a central-composite-design design-of-experiments method. The experiments were performed on a single-cylinder diesel research engine operating in a mixing-controlled low-temperature combustion mode at high and moderate exhaust gas recirculation rates with a split fuel injection for all conditions. The experiments identified the potential of fuel metering control for optimising the hydrocarbon emissions in low-temperature combustion by showing the effects of the fuel control parameters on the fuel mixing quality and the emission formation mechanisms. The response surfaces created from the detailed statistical analysis give a potent visualisation of the constraints on low-temperature combustion operation. This in turn allowed improved prescription of combustion modifications with the potential to moderate the negative effects observed.